Study of Endometrium’s Histopathological Pattern in Abnormal Uterine Bleeding - Zainab Karim, Afia Afridi, Mohibullah Khan, Sadaf Sabah, Shabir Ahmed Orakzai, Siyab Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Women of all ages may experience AUB, which is one of the most common and difficult conditions to diagnose. The diagnosis and treatment of endometrial etiology of AUB are primarily reliant on endometrial histopathology. The study's main purpose was to see how common different endometrial histological patterns were in individuals with abnormal uterine bleeding of various ages, as well as to learn more about the endometrial causes of AUB and how to treat them. Methods: From March 2019 to February 2020, 300 patients were studied in the department of Gynecology. Demographic data was gathered and documented. Different endometrial patterns were seen when endometrial samples were submitted for histological analyses. Results: The majority of patients with abnormal uterine haemorrhage were between the ages of 41 and 50 (48.6%), and the majority of them were multipara. Women suffering from menorrhagia (42% of patients) were following by polymenorrhagia (15%), menometrorrhagia (10.6%), continuing vaginal bleeding (9.6%), Polymenorrhagia (9.3%), and postmenopausal bleeding (8.6%). 8.6% of the population 4.6 percentage point. The most common histological characteristics in atypical uterine haemorrhage were proliferative and secretory endometrium (37 percent and 30 percent, respectively). A 22.6% prevalence of endometrial hyperplasia was detected. Conclusion: Endometrial assessment is used to rule out premalignant illnesses and cancer in women of all ages, especially those in the perimenopausal and postmenopausal periods of life.